Jurimetria econômica : índice de eficiência operacional do Poder Judiciário do estado de Mato Grosso - Silva, Vera Lícia de Arimatéia (2020)
It was found that the population's dissatisfaction with the inefficiency of the Judiciary, in particular, the delay in the procedural procedures, has contributed to the increase of a crisis of confidence in the justice, which can be seen in the results of opinion polls. Considering the discontent of the users of the justice system, the research sought to assess the influence of transaction costs for the efficiency of the Judiciary Branch of Mato Grosso. Thus, it asks to know, to what extent are transaction costs important for the performance of the Judiciary? Based on the institutionalist theory of transaction costs, the analysis identified the operational and administrative variables that were related to the set of inefficiencies linked to the various procedures that involve the activities carried out by the agents that make up the judicial system. The work used the methodology of multivariate analysis with the aid of the factor analysis technique to identify the weights of the variables studied for efficiency. Based on the factor analysis, the Operational Efficiency Index (IEFO) was prepared, obtaining an analysis and considering the structures of the counties, their capacity to generate revenues and their transaction costs, in order to contribute to decision making. The estimated Operational Efficiency Index (IEFO) varies between 70.255 and 37.177, the higher the index, the greater the efficiency. In the sequence, a ranking of operational efficiency was elaborated among the counties of the state and, finally, with the methodology of the cluster analysis, the similarities between the counties were verified, and observing the characteristics of the clusters, some suggestions for improvement were proposed operational efficiency of each group of counties. As a differential, the research brought an analysis focused on the input variables (administrative and operational), including transaction costs, in order to highlight the difficulties of the judicial units in serving the jurisdiction and presenting ways to improve operational efficiency in the search greater speed in procedural procedures. Finally, the research found that transactional costs are important for institutional performance, having a strong influence on the efficiency of the Judiciary Branch of Mato Grosso.